Vacuolar deposition of recombinant proteins in plant vegetative organs as a strategy to increase yields. Issue 3 (4th May 2017) - Marin Viegas, Vanesa Soledad; Ocampo, Carolina Gabriela; Petruccelli, Silvana
ABSTRACT: Delivery of recombinant proteins to vegetative tissue vacuoles was considered inconvenient since this compartment was expected to be hydrolytic; nevertheless there is growing evidence that certain foreign proteins accumulate at high yields in vacuoles. For example avidin, cellulolytic enzymes, endolysin, and transglutaminases were produced at high yields when were sorted to leaf central vacuole avoiding the detrimental effect of these proteins on plant growth. Also, several secretory mammalian proteins such as collagen, α1-proteinase inhibitor, complement-5a, interleukin-6 and immunoglobulins accumulated at higher yields in leaf vacuoles than in the apoplast or cytosol. To reach this final destination, fusions to sequence specific vacuolar sorting signals (ssVSS) typical of proteases or proteinase inhibitors and/or Ct-VSS representative of storage proteins or plant lectins were used and both types of motifs were capable to increase accumulation. Importantly, the type of VSSs or position, either the N or C-terminus, did not alter protein stability, levels or pos-translational modifications. Vacuolar sorted glycoproteins had different type of oligosaccharides indicating that foreign proteins reached the vacuole by 2 different pathways: direct transport from the ER, bypassing the Golgi (high mannose oligosaccharides decorated proteins) or trafficking through the Golgi (Complex oligosaccharide containing proteins). In addition, some glycoproteins lacked of paucimannosidic oligosaccharides suggesting that vacuolar trimming of glycans did not occur. Enhanced accumulation of foreign proteins fused to VSS occurred in several plant species such as tobacco, Nicotiana benthamiana, sugarcane, tomato and in carrot and the obtained results were influenced by plant physiological state. Ten different foreign proteins fused to vacuolar sorting accumulated at higher levels than their apoplastic or cytosolic counterparts. For proteins with cytotoxic effects vacuolar sorted forms yields were superior than ER retained variants, but for other proteins the results were the opposite an there were also examples of similar levels for ER and vacuolar variants. In conclusion vacuolar sorting in vegetative tissues is a satisfactory strategy to enhance protein yields that can be used in several plant species.